Kaempferol inhibits the expression of α-hemolysin and protects mice from methicillin-resistant Staphylococcus aureus-induced lethal pneumonia. (January 2022) - Yin, Ning; Yang, Xin; Wang, Li; Zhang, Chi; Guan, Jiyu; Tao, Ye; Guo, Xuerui; Zhao, Yicheng; Song, Wu; Wang, Bingmei; Tang, Yong
Abstract: Staphylococcus aureus (S. aureus) is a common pathogenic bacterium that induces a variety of diseases in humans and animals. The significant pathogenicity of S. aureus is due to its expression of several virulence factors. Alpha-hemolysin (Hla) has attracted attention as a virulence factor in staphylococcal pathogenesis and has been the predominant focus of intense research. In this study, we found that kaempferol, a flavonoid compound, inhibited hemolysis at a low concentration (32 μg/mL) and exerted no effect on bacterial growth. Western blot and RT-qPCR assays further demonstrated that kaempferol downregulated the expression of Hla in S. aureus . We observed that kaempferol alleviated the damage from S. aureus Hla in A549 cells. More importantly, kaempferol showed a potent protective effect on mice pneumonia induced by MRSA, as evidenced by a significant improvement in the survival of mice, a reduction in the number of colonized colonies in lung tissue and a decrease in the pathological damage to lung tissues. In summary, the results demonstrate the protective effect of kaempferol on MRSA-induced lethal pneumonia in mice and indicate that kaempferol could be developed as a potential anti-MRSA drug. Highlights: Alpha-hemolysin is the essential virulence determinant in the pathogenesis of S. aureus -induced pneumonia. We identified that Kaempferol inhibited the expression of Alpha-hemolysin. Kaempferol treatment significantly protect mice from Staphylococcus aureus –induced pneumonia.